Device engineering of organic solar cells based on a boron subphthalocyanine electron donor molecule. (1st January 2023) - Ahmadpour, Mehrad; Prete, Michela; Aryal, Um Kanta; Petersen, Anne Ugleholdt; Ahmad, Mariam; Rubahn, Horst-Günter; Jespersen, Malte F; Mikkelsen, Kurt V; Turkovic, Vida; Nielsen, Mogens Brøndsted; Madsen, Morten
Abstract: A boron subphthalocyanine molecule has been employed as a novel electron donor in organic solar cells (OPVs), and optimized in terms of composition and device structure in small molecule solar cells. It is demonstrated that the power conversion efficiency (PCE) of the devices obtained by solution-processing in bulk heterojunction solar cells could be improved by one order of magnitude by changing the fabrication method to vacuum deposition, which promotes a better morphology in the OPV active layers. Importantly, upon insertion of an additional pristine C70 thin interlayer between the active layer and the hole transport layer the PCE was further improved, highlighting the importance of interfacial layer engineering in such subphthalocyanine small molecule OPVs.